Towards a relational conceptualization of empathy - Dijke, Jolanda van (Nursing philosophy, 2020)
Empathy is a fundamental concept in health care and nursing. In academic literature, it has been primarily defined as a personal ability, act or experience. The relational dimensions of empathy have received far less attention. In our view, individualistic conceptualizations are restricted and do not adequately reflect the practice of empathy in daily care. We argue that a relational conceptualization of empathy contributes to a more realistic, nuanced and deeper understanding of the functions and limitations of empathy in professional care practices. In this article, we explore the relational aspects of empathy, drawing on sources that offer a relational approach, such as the field of care ethics, the phenomenology of Edith Stein and qualitative research into interpersonal and interactive empathy. We analyse the relational aspects of three prevalent components of empathy definitions: the underlying ability or act (i.e. the cognitive, affective and perception abilities that enable empathy); the resulting experience (i.e. empathic understanding and affective responsivity) and the expression of this experience (i.e. empathic expression). Ultimately, we propose four inter-related understandings of empathy: (a) A co-creative practice based on the abilities and activities of both the empathizer and the empathee; (b) A fundamentally other-oriented experience; (c) A dynamic, interactive process in which empathizer and empathee influence each other's experiences; (d) A quality of relationships.